Study on a Polymer Profile Control Agent with Controllable Swelling Time - Xue Junjie; Guo Donghong; Hou Qingfeng; Sun Jianfeng (International Journal of Petroleum Technology, 2019)
The study provided a microsphere profile control agent, which can smoothly go deep into the stratum by using the hydrophobic shell structure as the “protective film”. While the solution time in simulated brine was prolonged, water molecules went deep into the inside of the microsphere particles through the pore structure, and combined with hydrophilic groups. Because of the combination, the microsphere polymer started to swell, and opened the shell into long chain for days, and then at the end, its hydrophilic-hydrophobic block groups were all exposed in the solution, which resulted in self-thickening property. The dissolution time after entering into the stratum, i.e. the shell “rupture” time can be controlled by adjusting the carbon chains length of hydrophobic groups in the synthetic process. The agent can not only prolong the depth of plugging and provide a stable plugging rate, but also enlarge the water swept volume after dissolution. This method can stabilize the oil production and control the water cut. The function of delayed thickening ability makes the stratum sealed but kept at a certain permeability.